The sacraments: a dogmatic treatise - Pohle, Joseph (Dogmatic theology, 1915)
v. 1. The Sacraments in general. Baptism. Confirmation -- v. 2. The Holy Eucharist -- v. 3. Penance -- v. 4. Extreme unction-Holy orders. Matrimony.